Women’s Initiatives and the Reform Movement of Lithuania (1988–1989) - Jurėnienė, Virginija; Purvaneckienė, Giedrė (Information & Media, 2022)
Over 30 years have passed since the beginning of the Reform Movement; however, women’s initiatives in the Reform Movement of Lithuania have not been analysed. Commemorating the anniversary of the Reform Movement, Seimas of the Republic of Lithuania declared 2018 as the year of the Reform Movement and highlighted the period of 1988-1990 as a period of great importance in the Lithuania history when Seimas of the Reform Movement acted as a partial yet legal democratic representative of the nation in the Soviet occupation system. The article analyses women’s engagement into the initiative groups of the Sąjūdis, their participation in the initiative group and congress. The aim of this article is to shed light on the role of women in the building of the Soviet Union and the specific nature of the activities of the women’s Sąjūdis, the degree of involvement, the problems raised and the solutions proposed. In order to achieve this goal, the archival material contained in the fund of the Lithuanian Perestroika Sąjūdis of the New Archive of the Lithuanian State, the fund of the Kaunas Movement of the Kaunas Regional State Archive, the periodical press of the time were analysed, and the following scientific research was made available.